THE IMPACT OF DIVIDEND POLICY ON FIRM PERFORMANCE IN CONSUMER PRODUCT AND TRADING/SERVICES SECTOR IN MALAYSIA - Shan, Lee Hui; Lai, Tan Kian; Mun, Har Wai (International Journal For Research In Business, Management And Accounting, 2021)
This paper is to study the connection between dividend policy and firm performance in both sector in consumer product and trading. The firms in consumer product and service sectors listed in Bursa Malaysia were randomly selected as the research sample. The study period is 2002 to 2011 and 200 firms were selected. The dependent variables are return on asset (ROA) and Tobin’s Q and independent variables are dividend yield and dividend payout. The control variables are board size, firm age, firm size, firm leverage and firm growth. The result of the study shows that there is no significant relationship between firm performance in term of ROA and Tobin’s Q with dividend policy in term of dividend yield for both sectors. However, there is positive correlation and significant relationship between firm performance in term of ROA and Tobin’s Q with dividend policy in term of dividend payout for both sectors. The impact of dividend policy has greater effect on firm performance of consumer product sector compare to trading/services sector. This might be due to the reason of consumer sector firms need to provide “sweet” dividend to investors to attract their interest in the share, in addition to make it as a way to advertise their product brand to boost the revenues, profit and market value of the firm.